Terracing and ridge planting enhances soil organic carbon stability on water-eroded farmland slopes in Northeast China - Zhu Zhengqing; Mark Henderson; Gu Ruiting; Zhang Zhi; Zheng Xiaotong; Gong Xiaojing; Li Shang; Zhang Jiaqi; Liu Binhui (CATENA, 2026)

Experimental investigation of ethane(R170) solubility in AB, PAG, and POE lubricants - Ruiting Lv; Ruikang Li; Zhihao Zhang; Jialiang Hua; Guogeng He (International Journal of Refrigeration, 2026)

Can unmanned aerial vehicle laser scanning serve as an effective alternative to traditional field methods for predicting tree growth in even-aged Chinese fir (Cunninghamia lanceolata) plantations? - Rui Li; Baoying Wang; Ruiting Liang; Zhidan Ding; Zhaoting Zhu; Yujun Sun (European Journal of Forest Research, 2026)

Seed-associated Pseudomonas enhance the growth of Ambrosia trifida - Xue Chen; Chunying Li; Chang Wang; Jieyu Yang; Ruiting Ju; Fengjuan Zhang; Jihua Wu (Plant and Soil, 2026)

From suppression to selection: Chlorination drives biofilm adaptation and resistance in raw water distribution systems - Xiuwen Li; Ruiting Li; Kaiqing Bian; Qing Zhou; Yang Pan; Peng Shi; Aimin Li (Water Research, 2026)

Efficient degradation vs. enhanced persistence: How soil nutrients drive divergent pesticide fates via microbial strategies on the Tibetan plateau - Ruiting Dong; Meiqi Jiang; Dan Yang; Jie Li; Ruigang Wang; Liping Weng; Yang Sun (Environmental Research, 2026)

Chemical distance outweighs phylogeny in VOC-mediated cross-species plant defense communication - Chaonan Wang; Danfeng Liu; Xiao Xu; Mingjun Gao; Jiawei Wang; Jieren Jin; Yupeng Geng; Ruiting Ju; Yi Wang; Xiaoming Lu; Jihua Wu; Bo Li (Science China Life Sciences, 2026)

Pan-cancer characterization of the pyrimidine catabolic enzyme UPB1 identifies a tumor-suppressive prognostic biomarker in skin cutaneous melanoma - Yingli Men; Yi Shao; Yongfeng Chen; Ping Wang; Yiyang Li; Zhenzhen Yang; Ruiting Feng; Hui Wang; Yinsen Song; Cong Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Optimization of Agrobacterium-mediated transformation of commercial heirloom tomato cultivars to develop novel traits via CRISPR/Cas9 genome editing - Jordan Oxendine; Elsa Ibarra-Reyes; Junchi Ma; Carrie Li; Sarah Baron; Allison E. Hwang; Ruiting Wang; Daniel Rodriguez-Leal (Planta, 2026)
Main conclusion Trait development for commercial heirloom tomatoes can be advanced by optimization of tissue culture and transformation via Agrobacterium and CRISPR/Cas9 mutagenesis. Abstract Genetic improvement using new genome editing approaches relies on the efficient delivery of the CRISPR/Cas system in the vegetable crop tomato. Previous protocols for tomato transformation have primarily focused on a handful of cultivars (M82, Ailsa Craig, Microtom, Sweet-100) with very little commercial relevance, and it is not clear if these protocols can be implemented directly in other commercially relevant varieties. Heirloom tomatoes are sought for their deep and diverse flavor but have not been subjected to systematic crop improvement via conventional breeding or biotechnology approaches such as transgenesis or genome editing. Therefore, we tested the transformation and regeneration capacity of six different heirloom cultivars known for their superior taste and market relevance in the US. Subsequently, we optimized rooting conditions and used the GRF4-GIF1 chimeric developmental regulator to successfully recover transgenic plants. Finally, we evaluated the efficiency of targeted genetic modification using the CRISPR/Cas9 genome editing system in several of these cultivars. We demonstrate that our optimizations led to successful transformation of several heirloom varieties, including the generation of edited plants for target genes modifying plant architecture and flowering time. Our results set the foundation for a biotechnology platform to deliver improved traits to local and regional heirloom varieties using genome editing.

Corrigendum to “Development of active sustainable films based on phytic acid and silicate/polyvinyl alcohol hybrid system for wrapping chicken meat” [Food Packaging and Shelf Life 54 (2026) 101720] - Chaoqun Li; Fanyu Meng; Yongyan Yang; Jingfei Wang; Ruiting Zhang; Chongruihan Li; Yue Wang; Jia Wang; Yan Gao; Shuangling Zhong; Xuejun Cui (Food Packaging and Shelf Life, 2026)

Dynamic polysaccharide-based organic nanocomposite hydrogel precisely mediates oral targeted therapy for colorectal cancer - Xinyang Chen; Nuo Li; Huazheng Cheng; Ying Zhang; Ruiting Pan; Qin Shen; Guoqing Yan (Carbohydrate Polymers, 2026)

SIRT6 inhibits intermittent hypoxia-induced lung injury by stabilizing NRF2 - Ruiting Qin; Zhijuan Liu; Ran Li; Yongxia Li; Yuan Yang; Li Ai (Tissue and Cell, 2026)

Exploring factors influencing the height growth of Cunninghamia lanceolata based on bootstrap bayesian network and random forest - Baoying Wang; Rui Li; Yujun Sun; Ruiting Liang; Zhaoting Zhu (Trees, 2026)

The role of easily biodegradable organic materials as soil biostimulants in mediating the rapid enhancement of soil aggregate stability - Zheng MA; Xinlei ZHANG; Yujian WANG; Luyao YANG; Ruiting GUO; Longtao TU; Zhenlun LI (Pedosphere, 2026)

Development of active sustainable films based on phytic acid and silicate/polyvinyl alcohol hybrid system for wrapping chicken meat - Chaoqun Li; Fanyu Meng; Yongyan Yang; Jingfei Wang; Ruiting Zhang; Chongruihan Li; Yue Wang; Jia Wang; Yan Gao; Shuangling Zhong; Xuejun Cui (Food Packaging and Shelf Life, 2026)

Biodegradable cellulose-based electrostatically assisted air filter with high filtration efficiency and low resistance for sub-micron PMs - Jingyi Nie; Yueqing Li; Tingting Jiao; Ruiting Yang; Meiyun Zhang (Chemical Engineering Journal, 2026)

Short-Chain Fatty Acids Mitigate Perinatal Methylmercury-Induced Cognitive Impairment Via Modulation of the Gut Microbiota Composition - Binqian Han; FangRen Li; Qin Lu; Ruiting Ran; Lianrui Li; Weiying An; Fang Chen; Wenjuan Wang (Biological Trace Element Research, 2026)

Phage-based biosensors: From recognition to signal transduction empowered by amplification strategies for detecting foodborne pathogens - Fan Li; Xinxin Jiang; Yizhao Zhang; Ruiting Yao; Haorui Zhu; Lihua Fan; Guoliang Li (Trends in Food Science & Technology, 2026)

Tempol suppresses ferroptosis and relieves chronic intermittent hypoxia-induced lung injury through the inhibition of TLR4 and activation of the Nrf2/GSH axis - Ran Li; Ruiting Qin; Zhijuan Liu; Xiaojie He; Dan Li; Li Ai (Tissue and Cell, 2026)

Deciphering the impacts of multi-source materials on semi-continuous anaerobic digestion of food waste: performance enhancement and mechanism analysis - Yongdong Chen; Ruiting Zhu; Fang Liu; Xiuxia Zhang; Shi Li; Li Gu; Jiancheng Shu (Journal of Environmental Management, 2026)

Biodegradable microplastics exert differential impacts from polyethylene on pesticide fate in soil-earthworm systems: insights into degradation selectivity and microbial mechanisms - Dan Yang; Ruiting Dong; Furong Fu; Lixia Zhao; Xiaojing Li; Huike Ye; Mohan Bai; Yang Sun (Environmental Pollution, 2026)

Construction of built-in electric field in Ru/Vo-NiCo2O4 heterostructure for efficient ethylene glycol oxidation reaction coupled nitrate to ammonia electrolysis - Jingwen Ma; Ruiting Wang; Jinhao Liu; Ying Tian; Junbin Li (Journal of Environmental Chemical Engineering, 2025)

Surface oxygen coverage-mediated *OOH modulation enables highly selective H2O2 electrosynthesis - Jinchao Xu; Wanying Wang; Yuang Shi; Huan Li; Tengyao Sun; Xiang Wan; Chunning Zhao; Ruiting Hao; Weichao Wang (Chemical Engineering Journal, 2025)

Preparation of AuSe-BNPs/CFME and its high-sensitivity simultaneous detection of caffeic acid and dihydrotanshinone I - Han Cheng; Yanbing Pan; Tao Fang; Uchkun Ishimov; Awais Ihsan; Abrar Hussain; Ruiting Tian; Wenwen Ma; Jun Li; Xianju Huang (Chemical Engineering Journal, 2025)

Manganese ore tailings packed electrochemical precipitation wall: A novel approach of phosphorus removal and mechanistic insights - Shaoqin Chen; Ruiting Zhu; Jiancheng Shu; Lu Li; Buxiao Kuang (Journal of Environmental Management, 2025)

Invasion legacy weakens the positive effect of plant genotype diversity on soil multifunctionality - Wei Song; Cai Cheng; Zekang Liu; Shumeng He; Shenggui Xue; Xue Chen; Jingru Zhang; Lejie Wu; Qun Zhang; Guiyao Zhou; Yann Hautier; Ruiting Ju; et al. (Plant and Soil, 2025)

Conditional Generative Adversarial Networks Enhance Atmospheric Thermodynamic Profile Retrieval from Ground-Based Microwave Radiometer Measurements - Disong Fu; Xia Li; Jingmiao Zhu; Dazhi Yang; Ruiting Liu; Hongrong Shi; Guangyu Gao; Xinlei Han; Xiang’ao Xia; Yunjie Xia; Maoling Ayitikan; Kai Cheng; et al. (Journal of Meteorological Research, 2025)

Experimental evaluation of the impact of CO2/N2 mixture on residual water saturation during CO2 storage in saline aquifer - Yi Li; Wendong Dan; Jiaqi Zhao; Zhikai Hu; Ruiting Suo; Liang Xue; Li He; Qingchun Yu (Journal of Contaminant Hydrology, 2025)

Diffusion of sodium ions based on the interactions between gum arabic and oral mucin: Effects from the molecular weight of gum arabic - Yanlei Li; Ruiting Chang; Lin Lu; Zhiming Gao; Yuehan Wu; Wenxin Jiang; Dan Yuan; Katsuyoshi Nishinari (Food Chemistry, 2025)

Polystyrene bead ingestion promotes atherosclerosis plaque progression via BMP signaling in mice - Na Yang; Bo Wu; Xiaoxue He; Junhu Ma; Longhao Dai; RuiTing Ma; Tingting Yang; Xiaoxi Ning; Xiaoyan Li; Shaobin Jia (Food and Chemical Toxicology, 2025)

Carbon stocks in two temperate Zostera meadows in the Yellow Sea, North China - Ruiting Gu; Sichao Pu; Jianwu Tang; Tingting Liu; Linjing Ren; Shaochun Xu; Shuo Yu; Xiuzhen Li; Ning Zhao (CATENA, 2025)

Biodegradable air filter with electrospun composite nanofibers and cellulose fibers dual network: Enhanced electrostatic adsorption, humidity resistance, and extended service life - Jingyi Nie; Binrong Sun; Tingting Jiao; Jianfei Liao; Meiyun Zhang; Ruiting Yang; Yueqing Li (Journal of Hazardous Materials, 2025)

Oligo-residual disease in metastatic ALK-positive NSCLC treated with alectinib - Xi Yang; Xiao Chu; Ruiting Ye; Jianjiao Ni; Ya Zeng; Yue Zhou; Qing Xia; Shengping Wang; Qiao Li; Shuai Liu; Zhengfei Zhu; Li Chu (Clinical & Experimental Metastasis, 2025)

Vacancy engineering in transition metal selenides for long-lasting and fast-charging Na-ion batteries - Changsheng An; Jialing Liu; Chen Xu; Chi Zhang; Ruiting Li; Shumin Zhang; Shiying Zhang; Jinbo Li; Chao Cai; Xing Ou (Chemical Engineering Journal, 2025)

Biofilm formation dynamics in long-distance water conveyance pipelines: Impacts of nutrient levels and metal stress - Yifan Hu; Ruiting Li; Kaiqin Bian; Qing Zhou; Yang Pan; Lin Ye; Aimin Li; Peng Shi (Water Research, 2025)

Three-dimensional ordered macroporous nitrogen-doped carbon for efficient adsorption of flavonoids from plant extraction - Chuanmao Li; Wenyuan Lyu; Ruiting Lin; Haoran Liu; Yingfei Wang; Datong Chen; Fengliang Wang; Yingwei Li (Chemical Engineering Journal, 2025)

The protective effect of two highly branched polysaccharides from corn silk fermented by Lactobacillus plantarum against acute liver injury - Yuxiang Wu; Ying Song; Ruiting Li; Ziyan Han; Liyin Li; Yishu Yan (Carbohydrate Polymers, 2025)

Ubiquitin-conjugating enzyme E2T confers chemoresistance of colorectal cancer by enhancing the signal propagation of Wnt/β-catenin pathway in an ERK-dependent manner - Bo Liu; Ruiting Liu; Xiaolong Zhang; Lifei Tian; Zeyu Li; Jiao Yu (Chemico-Biological Interactions, 2025)

Cropland Exposure to Extreme Dryness and Wetness in China Under Shared Socioeconomic Pathways - Ruiting Yang; Guojie Wang; Yunxia Zhang; Peng Zhang; Shijie Li; Pedro Cabral (International Journal of Climatology, 2025)
Global warming by human activities have exacerbated the occurrence of extreme climatic events, which have taken a huge toll on human production and livelihoods. Predicting future changes in extreme wetness and dryness, along with the extent of cropland exposure to these conditions under various scenarios, is essential for effective climate adaptation and achieving sustainable development goals. This study employs the Standardised Antecedent Precipitation Evapotranspiration Index (SAPEI) method to identify extreme dryness and extreme wetness in China for future projections (2021–2100), and to analyse the characteristics of changes in the pixel‐day, intensity, and affected area by extreme dryness and wetness, as well as the cropland exposures to them under different shared socioeconomic pathways (SSPs). We find that the intensity and spatial extent of extreme dryness and wetness significantly increase in future climate projections, especially under high‐emission scenario compared to low‐emission scenario. Under the scenarios with increased emissions, the cropland exposure increased in most parts of China. Therefore, it is particularly urgent to keep the low‐emission scenario in order to minimise the cropland damage caused by extreme drought and wetness in China in the future.

Room temperature oxygenated groups addition in carbon materials via ozone oxidation for boosting electrochemical H2O2 production - Jinchao Xu; Wanying Wang; Yuang Shi; Huan Li; Ruiting Hao; Gang Chen; Wen Wang; Chunning Zhao; Weichao Wang (Chemical Engineering Journal, 2024)

Tree characteristics, drought and microtopography modulate the response of subtropical Cunninghamia lanceolata to drought - Ruiting Liang; Yujun Sun; Zhaoting zhu; Rui Li (European Journal of Forest Research, 2024)

A multi-layer antimicrobial cellulose filter with electrostatic adsorption properties prepared by coating cellulose with chitosan and CuO - Jingyi Nie; Jianfei Liao; Tintin Jiao; Binron Sun; Meiyun Zhang; Ruiting Yang; Yueqing Li (Chemical Engineering Journal, 2024)

Effectiveness of thinning in mitigating post-drought legacy effects on Chinese fir in subtropical plantation forests, Southeastern China - Ruiting Liang; Yifu Wang; Yujun Sun; Zhaoting zhu; Rui Li (Dendrochronologia, 2024)

Layered deposited MoS2 nanosheets on acorn leaf like CdS as an efficient anti-photocorrosion photocatalyst for hydrogen production - Yao Wang; Tengyang Gao; Ruiting Li; Yan Chen; Wen Luo; Yang Wu; Yu Xie; Yong Wang; Yifan Zhang (Fuel, 2024)

Associations of environmental cadmium exposure with kidney damage: Exploring mediating DNA methylation sites in Chinese adults - Yuan Wei; Xiaochen Wang; Qi Sun; Wanying Shi; Wenli Zhang; Xu Gao; Yawei Li; Ruiting Hao; Xiaojie Dong; Chen Chen; Kangning Cao; Weilong Jiang; et al. (Environmental Research, 2024)

Strengthening the diffusion of sodium ions by interactions between gum Arabic and oral mucin - Yanlei Li; Ruiting Chang; Duanyang Zhu; Lin Lu; Zhiming Gao; Yuehan Wu; Wenxin Jiang; Dan Yuan (Food Hydrocolloids, 2024)

Transcriptome and small RNA analysis unveils novel insights into the C4 gene regulation in sugarcane - Xiuting Hua; Zhen Li; Meijie Dou; Yanqing Zhang; Dongxu Zhao; Huihong Shi; Yihan Li; Shuangyu Li; Yumin Huang; Yiying Qi; Baiyu Wang; Qiyun Wang; et al. (Planta, 2024)

Expedite extraction of Pb2+ from low-strength wastewater in the half-wave rectified alternating current electrochemical method by accelerating lead electrodeposition kinetics - Tongtong Yue; Ruiting Wang; Yutong Zhong; Benzheng Li; Shuang Lv; Wei Feng (Journal of Cleaner Production, 2024)

Unraveling the generation mechanism of singlet oxygen in Bi2WxMo1-xO6 solid solution and roles in photocatalytic degradation of gaseous toluene under visible-light irradiation - Shaobo Cao; Lei Wu; Jun Li; Yang Li; Kang Da; Wenting Chen; Ruiting Xue; Jian Yang; Ximei Fan (Journal of Environmental Chemical Engineering, 2024)

Transcriptome analysis of Schizothorax oconnori (Cypriniformes: Cyprinidae) oocytes: The role of K+ in promoting yolk globule fusion and regulating oocyte maturation - Jianshe Zhou; Shuaijie Sun; Ruiting Li; Huifeng Xu; Ming Li; Zhichao Li (Fish Physiology and Biochemistry, 2024)

Plant stoichiometric hierarchical responses to nutrient enrichment can enhance understanding regarding the process of biodiversity loss - Xiaomei Sun; Duanhong Bao; Huan Li; Ruiting Zhao; Jinxia Li; Jieru Yu; Junhu Su (Ecological Engineering, 2024)

Scrub-vegetation cover impact on soil water migration and temperature change during freeze–thaw events in sandy desert soils of northwest China - Shuai He; Chengfu Zhang; Fan-Rui Meng; Charles P.-A. Bourque; Zhenying Huang; Xiang Li; Ruiting Jia (CATENA, 2024)

Effects of Chaihu Shugan San on Brain Functional Network Connectivity in the Hippocampus of a Perimenopausal Depression Rat Model - Ruiting Huang; Min Gong; Xue Tan; Jianying Shen; You Wu; Xiaoshi Cai; Suying Wang; Li Min; Lin Gong; Wenna Liang (Molecular Neurobiology, 2024)

Genotype diversity enhances invasion resistance of native plants via soil biotic feedbacks - Cai Cheng; Zekang Liu; Qun Zhang; Xing Tian; Ruiting Ju; Bo Li; Mark van Kleunen; Jonathan M. Chase; Jihua Wu (Ecology Letters, 2024)
Although native species diversity is frequently reported to enhance invasion resistance, within‐species diversity of native plants can also moderate invasions. While the positive diversity–invasion resistance relationship is often attributed to competition, indirect effects mediated through plant–soil feedbacks can also influence the relationship. We manipulated the genotypic diversity of an endemic species, Scirpus mariqueter , and evaluated the effects of abiotic versus biotic feedbacks on the performance of a global invader, Spartina alterniflora . We found that invader performance on live soils decreased non‐additively with genotypic diversity of the native plant that trained the soils, but this reversed when soils were sterilized to eliminate feedbacks through soil biota. The influence of soil biota on the feedback was primarily associated with increased levels of microbial biomass and fungal diversity in soils trained by multiple‐genotype populations. Our findings highlight the importance of plant–soil feedbacks mediating the positive relationship between genotypic diversity and invasion resistance.

Individual and interactive effects of air warming and elevated O3 on carbon fixation and allocation in two urban tree species - Yijing Wang; Sheng Xu; Bo Li; Yan Li; Ruiting Wang; Wei Chen; Xingyuan He; Felicity Hayes; Maihe Li (Agricultural and Forest Meteorology, 2024)

An attomolar-level electrochemical DNA biosensor based on target-triggered and entropy-driven catalytic amplification integrated with AuNPs@ZIF-8 nanocomposites for oral cancer overexpressed 1 detection - Jing Li; Qi Jiang; Minhui Chen; Wei Zhang; Ruiting Liu; Jin Huang; Qin Xu (Analytica Chimica Acta, 2024)

Permeability–Friction Relationships for Propped Fractures in Shale - Jiayi Yu; Jiehao Wang; Yan Li; Amr El-Fayoumi; Ruiting Wu; Xiaolong Liu; Peggy Rijken; Andrew P. Rathbun; Derek Elsworth (Rock Mechanics and Rock Engineering, 2023)

Molecular Identification and Expression Analysis of an Intelectin Gene in the Yellow Catfish Pelteobagrus fulvidraco (Siluriformes: Bagridae) - Senhao Jiang; Yuting Lei; Yanxuan Li; Wanyan Sun; Ti Wang; Ruiting Ma; Qiuning Liu; Boping Tang (Fishes, 2023)
Intelectins (ITLNs) are a family of calcium-dependent lectins with carbohydrate-binding capacity, are distributed across various vertebrates, and play an important role in the innate immune response against pathogen infection. The yellow catfish Pelteobagrus fulvidraco (Siluriformes: Bagridae) is an economically important fish in China. The aim of this study was to quantify the gene expression of ITLN in response to pathogen-associated molecular patterns (PAMPs) stimulation. Here, the ITLN gene of P. fulvidraco was characterized and named PfITLN. The full-length cDNA of PfITLN was 1132 bp, including a 5’-untranslated region (UTR) of 140 bp, a 3’-UTR of 110 bp, and an open reading frame (ORF) of 882 bp encoding a polypeptide of 293 amino acids, which contains a signal peptide and two fibrinogen-related domains (FReDs). PfITLN had a molecular weight of 32.39 kDa with a theoretical pI of 5.03. The deduced PfITLN amino acid sequence had 81%, 64%, and 55% homology with Ictalurus furcatus, Danio rerio, and Homo sapiens, respectively. Moreover, the predicted tertiary protein structure of PfITLN was highly similar to that of other animals, and phylogenetic analysis showed that the PfITLN protein was close to those of other Teleostei. Real-time quantitative reverse transcription-PCR (qRT-PCR) analysis showed PfITLN expression in all examined tissues, with the highest abundance seen in the liver, followed by the head kidney, spleen, trunk kidney, and muscle. After PAMP infection with lipopolysaccharide (LPS) and polyriboinosinic polyribocytidylic acid (poly I:C), the expression levels of PfITLN were significantly upregulated at different time points. These results suggested that PfITLN might be involved in innate immunity.

The role of total antioxidant capacity and malondialdehyde of seminal plasma in the association between air pollution and sperm quality - Lipeng Li; Tengfei Feng; Ruiting Wu; Yaling Zhang; Ning Wang; Mengqi Wu; Yaxian Pang; Sujuan Yang; Aimin Yang; Dengsuo Zhang; Guimin Hao; Rong Zhang (Environmental Pollution, 2023)

Performance analysis of two-stage CO2 transcritical refrigeration cycles with absorption subcooling and mechanical recooling - Caoxuheng Huang; Zeyu Li; Zhihao Ye; Ruiting Wang (International Journal of Refrigeration, 2023)

Association between meteorological factors and COVID-19 transmission in low- and middle-income countries: A time-stratified case-crossover study - Yu Wang; Yiran Lyu; Shilu Tong; Cheng Ding; Lan Wei; Mengying Zhai; Kaiqiang Xu; Ruiting Hao; Xiaochen Wang; Na Li; Yueyun Luo; Yonghong Li; et al. (Environmental Research, 2023)

High adhesion hydrogel electrolytes enhanced by multifunctional group polymer enable high performance of flexible zinc-air batteries in wide temperature range - Zhihao Shang; Hang Zhang; Mengfei Qu; Ruiting Wang; Li Wan; Da Lei; Zhengzheng Li (Chemical Engineering Journal, 2023)

Linear charging-discharging of an ultralong UVA persistent phosphor for advanced optical data storage and wide-wavelength-range detector - Chuanlong Wang; Yahong Jin; Jiaxin Zhang; Xiangguang Li; Haoyi Wu; Ruiting Zhang; Qing Yao; Yihua Hu (Chemical Engineering Journal, 2023)

The impacts of urban anthropogenic heat and surface albedo change on boundary layer meteorology and air pollutants in the Beijing-Tianjin-Hebei region - Ruiting Liu; Zhiwei Han; Jiawei Li; Jie Li; Lin Liang; Yunfei Wu (Urban Climate, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Impact of Coreopsis tinctoria Nutt. Essential oil microcapsules on the formation of biogenic amines and quality of smoked horsemeat sausage during ripening - Yazhuo Li; Yukun Geng; Di Shi; Ruiting Li; Juan Tang; Shiling Lu (Meat Science, 2023)

Fine-mapping and candidate gene analysis of qFL-c10-1 controlling fiber length in upland cotton (Gossypium hirsutum L.) - Ruiting Zhang; Chao Shen; De Zhu; Yu Le; Nian Wang; Yuanxue Li; Xianlong Zhang; Zhongxu Lin (Theoretical and Applied Genetics, 2022)

White Matter Free Water is a Composite Marker of Cerebral Small Vessel Degeneration - Peiyu Huang; Ruiting Zhang; Yeerfan Jiaerken; Shuyue Wang; Hui Hong; Wenke Yu; Chunfeng Lian; Kaicheng Li; Qingze Zeng; Xiao Luo; Xinfeng Yu; Xiao Wu; et al. (Translational Stroke Research, 2022)

Effect of different carboxymethyl cellulose structure parameters on tartrates stability of red wine: viscosity and degree of substitution - Haiyan Ding; Ruiting Hou; Yun Li; Beibei Zhang; Baobao Zhao; Kun Liu (Food Additives & Contaminants: Part A, 2020)

Semi-synthetic product dihydroartemisinin inhibited fibronectin-1 and integrin-β1 and interfered with the migration of HCCLM6 cells via PI3K-AKT pathway - Ruiting Wu; Yan Gao; Jiaqin Wu; Chunli Wang; Li Yang (Biotechnology Letters, 2020)

Perfusion Changes of Unexplained Early Neurological Deterioration After Reperfusion Therapy - Jingjing Fu; Ying Zhou; Qingqing Li; Genlong Zhong; Sheng Zhang; Ruiting Zhang; Chang Liu; Minming Zhang; Min Lou (Translational Stroke Research, 2020)

The assessment of different vegetation indices for spatial disaggregating of thermal imagery over the humid agricultural region - Kai Liu; Shudong Wang; Xueke Li; Yao Li; Bo Zhang; Ruiting Zhai (International Journal of Remote Sensing, 2020)

Responses of soil biota and nitrogen availability to an invasive plant under aboveground herbivory - Jiahui Zhou; Ruiting Ju; Bo Li; Jihua Wu (Plant and Soil, 2017)

Origin of the Lengshuigou porphyry–skarn Cu deposit in the Zha-Shan district, South Qinling, central China, and implications for differences between porphyry Cu and Mo deposits - Guiqing Xie; Jingwen Mao; Ruiting Wang; Deming Meng; Jia Sun; Junzhi Dai; Tao Ren; Jianbi Li; Haijie Zhao (Mineralium Deposita, 2017)

A one-step ligation system for rapid generation of armed, conditionally-replicating adenoviruses - Xing Li; Ruiting Xia; Jing Zhao; Dongyang Wang; Qinwen Mao; Haibin Xia (Biotechnology Letters, 2013)